The prisms of gramsci : the political formula of the United Front - Del Roio, Marcos (Historical materialism book series, 2015)
In this work, Marcos Del Roio analyses Gramsci's pre-prison political-theoretical activity in light of a radical thesis: that throughout Gramsci's life we see a total continuity between his political praxis and his philosophical reflection. That is not to ignore the changes, turns, and even fractures in the Sardinian communist's thinking across his brief but rich existence. On the contrary. Reading Gramsci, we find key ideas that set the rhythm of all of his thought, at least from the time of the Turin factory councils up till the writing of his final notebooks. These ideas also established the essential identity of his thinking, throughout (and over and above) the diversity of its manifestations: just as we typically find in all great thinkers. This book's title, referring to the metaphor of a ray of light passing through a prism, expresses this counterpoint between identity and diversity. The main category we find in the subtitle speaks to this same problematic, considered in the context of Gramsci's political action and the radical Leninism that guided him in his victorious battle with Bordiga: the 'united front'. This political formula was coined in Germany in 1921 and was central to the late Lenin's thinking, and in this work Del Roio shows its various different interpretations as the basis for analysing Gramsci's own position in this regard.